2019
DOI: 10.1002/mp.13434
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the local biomechanical environment of liver tumors in vivo

Abstract: Purpose: Biomechanical properties can be used as biomarkers to diagnose tumors, monitor tumor development, and evaluate treatment efficacy. The purpose of this preliminary study is to characterize the biomechanical environment of two typical liver tumors, hemangiomas (HEMs) and hepatocellular carcinomas (HCCs), and to investigate the potential of using strain metrics as biomarkers for tumor diagnosis, based on a limited clinical dataset. Methods: Magnetic resonance (MR) tagging was used to quantify the motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Cazoulat et al (2021) demonstrated that the lung stress map derived from the FEM-based deformable image registration (DIR) was significantly correlated with a ventilation Tc-99m SPECT image. Several studies have estimated the elasticity of the liver tissue with natural motion using biomechanics (Watanabe et al 2010, Ma et al 2019. In one recent study, the authors constructed an FEM-based biomechanical model that estimates the liver elasticity map using respiratory-induced liver displacement from routine clinical four-dimensional computed tomography (CT) (Fujimoto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cazoulat et al (2021) demonstrated that the lung stress map derived from the FEM-based deformable image registration (DIR) was significantly correlated with a ventilation Tc-99m SPECT image. Several studies have estimated the elasticity of the liver tissue with natural motion using biomechanics (Watanabe et al 2010, Ma et al 2019. In one recent study, the authors constructed an FEM-based biomechanical model that estimates the liver elasticity map using respiratory-induced liver displacement from routine clinical four-dimensional computed tomography (CT) (Fujimoto et al 2021).…”
Section: Introductionmentioning
confidence: 99%